PENGARUH LATIHAN PLYOMETRIC DEPTH JUMP DAN JUMP TO BOX TERHADAP POWER OTOT TUNGKAI PADA PEMAIN EKSTRAKURIKULER BOLAVOLI SMK TEKNOLOGI NASIONAL MALANG - Hidayat, Taufik; Saichudin, Saichudin; Kinanti, Rias Gesang (Jurnal Sport Science, 2017)
ABSTRACT :This research was to know reveal: (1) the effect of depth jump to the improvement of limb muscle power; (2) the effect of jump to box training to the improvement of limb muscle power; (3) the difference between depth jump and jump to box training to the improvement of limb muscle power, by using research plan the static grup pretest-posttest design. The Sample of research the old for 20 athletes age 16-17 years, be divided two group that is: depth jump training group and jump to box training group. Prosesing of research data pretest and posttest by doing test vertical jump. Sample be given treatmen depth jump training and jump to box training for 8 sunday by frequency training 3 time of Sunday. Result of analysis test using One Way Anova, it was obtained F calculation value of squat training group = 12.183and leg press training group = 12815; p value for depth jump training group = 0.03< 0.05 and p value for jump to box training group 0.02< 0.05. From the result above, it showed that p value < 0.05 which means Ho rejected. Thus, there was significant difference between squat training and leg press training to the improvement of limb muscle strength. From calculation of mean be obtained resulted depth jump trainingÂ mean = 4410.450than jump to box be obtained mean = 4470.050. So that be concluded that jump to box training group more increase of limb muscle strength than depth jump training group.Key words :depth jump training, jump to box training, power, limb muscle, plyometric, volleyball